Intrarenal Expression of miRNAs in Patients With Hypertensive Nephrosclerosis - Wang, Gang; Kwan, Bonnie Ching-Ha; Lai, Fernand Mac-Moune; Choi, Paul Cheung-Lung; Chow, Kai-Ming; Li, Philip Kam-Tao; Szeto, Cheuk-Chun (American journal of hypertension, 2010)
Background MicroRNAs (miRNAs) are non-coding, single-stranded RNA molecules that play important roles in a number of physiological and pathological processes. Previous studies showed that miRNAs targeting transcription factors ZEB1 and ZEB2 may repress epithelial–mesenchymal transition (EMT). Methods We studied 34 consecutive patients with biopsy-proven hypertensive nephrosclerosis. Intrarenal expression of miR-200 family, miR-205, and miR-192 were determined. We also studied normal renal tissue from 20 patients with nephrectomy for kidney cancer as controls. Results The level of intrarenal of miR-200a, miR-200b, miR-141, miR-429, miR-205, and miR-192 were significantly higher in patients with hypertensive nephrosclerosis than controls. Proteinuria correlated with intrarenal expression of miR-200a (r = 0.594, P < 0.001), miR-200b (r = 0.395, P = 0.004), miR-141 (r = 0.377, P = 0.007), miR-429 (r = 0.346, P = 0.013), miR-205 (r = 0.636, P < 0.001), and miR-192 (r = 0.306, P = 0.029). Estimated glomerular filtration rate (GFR) correlated with intrarenal expression of miR-200a (r = −0.374, P = 0.007) and miR-205 (r = −0.400, P = 0.005). Intrarenal expression of ZEB1 inversely correlated with intrarenal expression of miR-429, whereas expression of ZEB2 inversely correlated with miR-200a, miR-200b, and miR-429. Conclusions The results show that intrarenal expression of miR-200a, miR-200b, miR-141, miR-429, miR-205, and miR-192 were increased in hypertensive nephrosclerosis, and the degree of upregulation correlated with disease severity. The results suggested that these miRNA species may play important roles in the pathogenesis of hypertensive nephrosclerosis.